Paroxysmal states in internal diseases - Borisenko, O. A.; Zaitseva, T. A.; Stoyanov, A. N.; Kolesnik, E. O. (Journal of Education, Health and Sport, 2017)
Borisenko О. А., Zaitseva T. A., Stoyanov A. N., Kolesnik Е. О. Paroxysmal states in internal diseases. Journal of Education, Health and Sport. 2017;7(1):437-448. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.293018 http://ojs.ukw.edu.pl/index.php/johs/article/view/4273 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. PAROXYSMAL STATES IN INTERNAL DISEASES О. А. Borisenko, T. A. Zaitseva, A. N. Stoyanov*, Е. О. Kolesnik* RegionalHospital, Nikolaev *OdessaNationalMedicalUniversity Summary This article provides information about paroxysmal disorders of consciousness in a number of somatic diseases considered. Presents clinical cases of paroxysmal disorders of consciousness with decompensated conditions: lung disease, liver and thyroid. The work will be useful for a wide range of doctors, especially specialists in family medicine. Key words: paroxysmal disorders of consciousness, somatoneurology, pulmonary, hepatic, thyrotoxic encephalopathy.